Aandaakonan inaakonigewin: Considering an Anishinaabe meaning to the Canadian law on consultation and accommodation - Guido, Veronica Ann (2021)
Indigenous laws are resurging throughout Turtle Island and have vital roles to play in the creation and application of laws, governance structures, and decision-making. However, for this to happen, the understanding of the law which is predominant and dictates legal processes must change, specifically when such laws apply to Indigenous land and peoples. This will allow Indigenous legal orders – including Anishinaabe legal norms such as mutual aid, kinship, giftedness and doodem – to flourish. This thesis explores Anishinaabe law resurgence by asking: how can decision-making about land, natural resources, and Aboriginal rights through the duty to consult and accommodate be altered so to be understood and applied through Anishinaabe law? By exploring the legal principles and theories that form both the colonial and Anishinaabe legal orders, this thesis considers one way Anishinaabe legal orders could understand the duty to consult and accommodate.